The Impact of Marketing on Customer Loyalty: A Study of Dutch Lady in Malaysia - Daisy Mui Hung Kee; Raemathy Murthy; Raghavi Ganasen; Rasitraa Ru Lingam; Raveen Chandran (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2021)
Dutch Lady Milk Industries Berhad is one of the most successful manufacturers and suppliers of dairy products in Malaysia. Dutch Lady supplies dairy products packed with essential nutrients and vitamins for people of all ages, ranging from infants to adults. This study aims to investigate the impact of marketing on customer loyalty. A survey through Google form was conducted among different age group people to identify the most effective Dutch Lady's marketing tools. This study showed that one of the most effective marketing tools used by Dutch Lady in Malaysia is 'free samples' under promotion tools that help consumers raise brand awareness and reach the target audience. It also helps to retain customers and create customer loyalty. Therefore, the Dutch Lady should invest more marketing strategies in giving out free samples to potential and current customers.